2006
DOI: 10.1002/jcb.20825
|View full text |Cite
|
Sign up to set email alerts
|

Role of amino acids in translational mechanisms governing milk protein synthesis in murine and ruminant mammary epithelial cells

Abstract: The role of amino acids (AA) on translational regulation in mammary epithelial cells cultured under lactogenic conditions was studied. The rates of total protein synthesis and beta-lactoglobulin (BLG) synthesis in mouse CID-9 cells were 2.1- or 3.1-fold higher, respectively, than in their bovine L-1 counterparts. Total AA deprivation or selective deprivation of Leu had a negative protein-specific effect on BLG synthesis that was more pronounced in bovine cells than in murine cells. Dephosphorylation of eukaryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 56 publications
8
62
0
Order By: Relevance
“…According to previous reports, Leu was involved in cell growth and differentiation through the mTOR pathway (Proud, 2007;Stipanuk, 2007). Moreover, Leu produced a dosedependent regulation of mTOR and served as a key intracellular regulatory factor of the mTORC1 pathway in CMECs (Moshel et al, 2006;Prizant and Barash, 2008;Appuhamy et al, 2012;Durán and Hall, 2012). Kim et al (2001) found that His was the first limiting factor for milk protein secretion.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…According to previous reports, Leu was involved in cell growth and differentiation through the mTOR pathway (Proud, 2007;Stipanuk, 2007). Moreover, Leu produced a dosedependent regulation of mTOR and served as a key intracellular regulatory factor of the mTORC1 pathway in CMECs (Moshel et al, 2006;Prizant and Barash, 2008;Appuhamy et al, 2012;Durán and Hall, 2012). Kim et al (2001) found that His was the first limiting factor for milk protein secretion.…”
Section: Introductionmentioning
confidence: 93%
“…When activated by AAs, mTORC1 in turn catalyzed S6K1 and 4EBP1 phosphorylation, followed by phosphorylating the ribosomal protein S6 (RPS6) (Wang and Proud, 2006). S6K1 was a target of mTOR activated in Thr 389 whose phosphorylation status was a main indicator of the AA-induced mTORC1-activated signaling pathway (Moshel et al, 2006;Prizant and Barash, 2008;Appuhamy et al, 2012;Arriola Apelo et al, 2014c). In addition, phosphorylation of 4EBP1 by mTOR increased the initial reaction rates (Beugnet et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine mammary acini cultured in lactogenic hormones and in a nutrient-rich medium (i.e., high glucose and 4-fold the concentration of amino acids found in plasma of well-fed cows) had an increase of S6K1 and 4EBP1 phosphorylation and dissociation between 4EBP1 and eIF2E [29]. Mixtures of all AA or Leu alone in medium strongly affects synthesis of beta-lactoglobulin in mammary epithelial cells of the mouse and the cow, with all AA being more potent than Leu alone [162]. The latter study demonstrated that synthesis of beta-lactoglobulin in bovine cells was associated with phosphorylation of 4EBP1 and S6K1 and that the major effect on protein synthesis of all AA or Leu was through mTOR.…”
Section: How Insulin and Mtor Cross-talk Control Translation Of Milk mentioning
confidence: 99%
“…One of the most important components of milk proteins is the functional group of immuneactive AAs, which, in addition form the immune active proteins of the body, accelerate the production of T-lymphocytes, specific antibodies, and also have their own immunological activity and are perspective as immune modulators (Niven et al,1998;Moshel et al, 2006;Mazhitova et al, 2015). The highest amount of immune-active AAs was in the milk protein of crossbred cows at the crosses of URS with Montbeliarde breeds cows, this indicator was 501.6 mg/g, which is by 9.6 242 J.Indonesian Trop.Anim.Agric.…”
Section: Resultsmentioning
confidence: 99%